Rorty’s metaphilosophy and the critique of epistemology - Pešić, Boško (Array, 2020)
Richard Rorty is a contemporary philosopher of analytic philosophical tradition who shifted his career to a metaphilosophical critique of epistemology. The basis for Rorty’s critique lies in his rejection of Cartesian dualism, which leads him to a conclusion that every attempt at achieving truth by the way of knowing essences is destined for failure. Instead, Rorty argues for a search for understanding via conversation – a process which he called edification – and which would lead to the elimination of the epistemological problem of knowledge altogether. His metaphilosophical endeavor wants hermeneutics to supplant epistemology and become the fundamental philosophical approach. However, Rorty underemphasizes the importance of truth for hermeneutics, a deficiency of his which the paper will try to amend in order to show that Rorty’s skepticism regarding truth makes it problematic for his position to claim rapport with hermeneutics. After detailing Rorty’s metaphilosophical programme, which was mainly established in Philosophy and the Mirror of Nature, the paper will explore the (in)compatibility of his position with hermeneutics, most notably with Gadamer’s. This leads to the conclusion that it would be a mistake to consider Rorty’s (meta)philosophy as an offshoot of hermeneutics or being completely compatible with it, considering he gives primacy to social problems over truth.